Norovirus P particle: a subviral nanoparticle for vaccine development against norovirus, rotavirus and influenza virus. (June 2012) - Tan, Ming; Jiang, Xi
Noroviruses (NoVs) are important pathogens causing epidemic acute gastroenteritis that affects millions of people worldwide. The protruding (P) domain of the NoV capsid protein, the surface antigen of NoV, forms a 24-mer subviral particle called the P particle that is an excellent candidate vaccine against NoVs. The P particles are easily produced in Escherichia coli, highly stable and highly immunogenic. Each P domain has three surface loops that can be used for foreign antigen presentation, making the P particles a useful platform for vaccine development against other infectious diseases. This article summarizes the discovery, structure, development and applications of the P particles as a vaccine against NoVs, as well as a vaccine platform against rotavirus, influenza virus and possibly other pathogens in the future.